Use of contrast-enhanced ultrasonography for the detection of a feline insulinoma. Issue 2 (September 2019) - Cervone, Mario; Harel, Mathieu; Ségard-Weisse, Emilie; Krafft, Emilie
Case summary: A 14-year-old cat was presented with a 2-week history of ataxia, seizure-like episodes, vomiting and weight loss. Serum biochemistry revealed severe hypoglycaemia, associated with low serum fructosamine and high insulin concentrations. On abdominal ultrasound, a focal hypoechoic well-defined mass in the left limb of the pancreas was identified and the presence of an additional smaller nodule was suspected. Contrast-enhanced ultrasonography (CEUS) confirmed the presence of both lesions and revealed a third, even smaller nodule. Partial pancreatectomy was performed. Histopathology and immunohistochemistry confirmed the presence of a multifocal insulinoma. Six months later, the cat presented with tenesmus and obstipation. A colorectal adenocarcinoma was diagnosed with histopathology after partial excision of a colorectal mass. The cat was euthanased a month later owing to recurrent episodes of severe obstipation. Relevance and novel information: This is the first clinical description of the use of CEUS in the diagnosis of feline insulinoma. Furthermore, the available scientific literature on feline insulinoma was reviewed.